Development Of An Interactive Plant Monitoring Device By Using Arduino Microcontroller - Mohd Zabidi, Muhammad Izzat Zakwan; Zainal Abidin, Amar Faiz; Harun, Mohamad Haniff; Azahar, Arman Hadi; Idrus, Muhammad Hazwan; Tengku Wook, Tg Mohd Faisal; Mohd Said, Rahaini; Hasim, Nur Aiman Hanis (Asian Research Publishing Network, 2021)
Gardener conveys a wide range of plants which will have fluctuating watering requirements for each plant must get the perfect measure of water. An unreasonable measure of water may keep the plant's underlying foundations from oxygen and thought to process them to decay; too less water and the plant will now not get hold of the nutrients in wishes to keep on existing. Besides, gardener mostly do not know how was the character shown by plant instead of pets where they could show their feeling when they are threatening. This experiment concentrated on the best way to build up a framework utilising Arduino that controls all the parameter required of plants life at the ideal time. Besides that, this project proposed as no automation needed as we want it to be interactively fun like playing a "Pou" game for real in terms of plants.